1999
DOI: 10.1007/s004380051071
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the cps1 gene provides evidence for a septation checkpoint in Schizosaccharomyces pombe

Abstract: The fission yeast gene cps1, which encodes the catalytic subunit of beta-glucan synthase, was isolated in a screen for mutants that show an increase in ploidy at the restrictive temperature. cps1 mutants display defects in both polarity and septation at the permissive temperature, and become swollen and multinucleate at the restrictive temperature. Analysis of the interaction of cps1 with other mutations suggests the existence of a septation checkpoint, which requires the activity of the protein kinase weel fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
145
0
7

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(157 citation statements)
references
References 46 publications
5
145
0
7
Order By: Relevance
“…Previous studies have shown that structural defects in the actomyosin ring are monitored via a checkpoint mechanism that involves the protein phosphatase Clp1p/Flp1p and the SIN (Le Goff et al, 1999;Liu et al, 1999Liu et al, , 2000Cueille et al, 2001;Trautmann et al, 2001;Mishra et al, 2004). We have shown that clp1⌬ displays an additive deleterious effect in combination with pdk1⌬, consistent with the idea that pdk1⌬ cells assemble structurally defective rings and that their maximal viability depends on Clp1p function.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies have shown that structural defects in the actomyosin ring are monitored via a checkpoint mechanism that involves the protein phosphatase Clp1p/Flp1p and the SIN (Le Goff et al, 1999;Liu et al, 1999Liu et al, , 2000Cueille et al, 2001;Trautmann et al, 2001;Mishra et al, 2004). We have shown that clp1⌬ displays an additive deleterious effect in combination with pdk1⌬, consistent with the idea that pdk1⌬ cells assemble structurally defective rings and that their maximal viability depends on Clp1p function.…”
Section: Discussionsupporting
confidence: 88%
“…In particular, it is interesting to note that Sid2p is related to members of the AGC family of kinases (Sparks et al, 1999;Tamaskovic et al, 2003) which are known to be regulated by PDK1 family members (Belham et al, 1999). However, the finding that SIN proteins participate in correcting defects associated with the cell division apparatus (Le Goff et al, 1999;Liu et al, 1999;Mishra et al, 2004) might provide an alternate explanation to the observed synthetic lethality between pdk1⌬ and SIN mutants.…”
Section: Discussionmentioning
confidence: 99%
“…However, because these studies are done at temperatures where there is still some residual SIN function, it is unclear whether the SIN is required for bulk septum synthesis. Although at high restrictive temperatures SIN mutants do not make septa, it is not clear if this is an indirect effect due to the disappearance of the actomyosin ring, which is required for localization of septum-synthesizing enzymes (Le Goff et al 1999;Liu et al 1999;Cortes et al 2002), making this issue difficult to resolve.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several enzymes involved in synthesis of 1,3-b-glucan and 1,3-a-glucan have been identified, and all of them are large integral membrane proteins. As 1,3-b-glucan synthase subunits, Cps1p/Bgs1p and Bgs4p are required for assembly of 1,3-b-glucan and thus of the primary septum (Le Goff et al 1999;Liu et al 1999;Cortes et al 2002Cortes et al , 2005. The enzyme complex involved in 1,3-b-glucan synthesis requires not only synthase subunits but also regulatory 1 subunit(s).…”
mentioning
confidence: 99%
“…The SIN triggers actomyosin ring contraction coordinated with the synthesis of the primary and secondary septa that will form the new cell wall (Krapp et al 2004;Wolfe and Gould 2005). The small GTPase Rho1 is known to promote cell-wall formation at the division site by stimulation of Cps1p/ Drc1 1,3-b-glucan synthase (Le Goff et al 1999), but the mechanism remains unclear.…”
Section: T He Fission Yeast Schizosaccharomyces Pombe Is a Lead-mentioning
confidence: 99%